2018
DOI: 10.1007/s11219-018-9407-9
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensibility of system models during test design: a controlled experiment comparing UML activity diagrams and state machines

Abstract: UML activity diagrams and state machines are both used for modeling system behavior from the user perspective and are frequently the basis for deriving system test cases. In practice, system test cases are often derived manually from UML activity diagrams or state machines. For this task, comprehensibility of respective models is essential and a relevant question for practice to support model selection and design, as well as subsequent test derivation. Therefore, the objective of this paper is to compare the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 56 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…Activity diagrams model workflow or business processes and operations internally. This diagram will describe processes in more detail than in the use case diagram 47 .…”
Section: Activity Diagrammentioning
confidence: 99%
“…Activity diagrams model workflow or business processes and operations internally. This diagram will describe processes in more detail than in the use case diagram 47 .…”
Section: Activity Diagrammentioning
confidence: 99%
“…Mendling et al [24] present a broad review on model comprehension studies in this area. Regarding other areas, recent work on model comprehensibility has been done in testing [25,26] ; Liebel and Tichy [27] performed a study comparing the comprehensibility of functional requirements modeled in different graphical modeling languages. Scanniello et al [28] reported an empirical study on how models help in the understanding of source code.…”
Section: Related Workmentioning
confidence: 99%
“…Several threats have arisen as a result of the empirical nature of the evaluation undertaken herein, challenging the theoretical rationale of the outcomes, necessitating a repeat of this research to confirm or deny the decisions. Internal validity (IV), external validity (EV), construct validity (CV), and reliability validity (RV) are the four main threats (Felderer & Herrmann, 2019;Miranda & Bertolino, 2018;Ouriques et al, 2018).…”
Section: Threats To Validitymentioning
confidence: 99%